Meningkatkan Keterampilan Menulis Bahasa Inggris melalui Teknik “Exposure Generalization Reinforcement and Use” - Muhammad Kahidir (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2023)
In learning English, especially in the aspect of writing, which is attended by students with various levels of ability, it seems that they show less activity and mastery of grammar and vocabulary is still weak. This deficiency has an impact on the low learning outcomes of students' writing in English. The purpose of this classroom action research is to improve students' writing skills and improve mastery of sentence patterns and vocabulary in students' English learning through the